Candesartan Mitigates Paclitaxel-Induced Peripheral Neuropathy in Human Neuron Cells: A Comprehensive in Vitro Evaluation - Karar H. Alfarttoosi; Ihsan S. Rabeea (Iraqi Journal of Pharmaceutical Sciences, 2025)
Paclitaxel (Taxol) belongs to the initial taxane category and is employed for treating diverse types of cancers, including ovarian, lung, and breast cancers. Paclitaxel is associated with the highest prevalence of peripheral neuropathy. The detection of PIPN may necessitate a reduction in dosage or discontinuation of treatment, which can have consequences for cancer care. Activation of AT2R has shown neuroprotective effects in different rodent models. this study aims to assess the potential impact of candesartan in mitigating the deleterious effect on human neuron cells. The methods involved in Immunocytochemistry to characterize the neuron cells depend on the expression of the B tubulin III protein. WST-8 test was used on human neuron cell culture to assess the individual and combined cytotoxicity and inhibition ratio (IR%) of Taxol and candesartan. The Chou-Talalay index (CI) equation was utilized to determine if the interaction was antagonistic, additive, or synergistic. As well as investigating the morphological change. The results, findings demonstrated a notable increase in the inhibitory ratio (IR%) when comparing Taxol to the control group at all serial concentrations, with statistical significance (P<0.05). on the other hand, candesartan did not show any significant difference compared to the control group (P>0.05). Interestingly, the combination treatment group showed a significant reduction in the inhibitory ratio (IR%) when compared to the Taxol group. the estimated Chou-Talalay indices (CI) values suggest a significant antagonistic interaction between Taxol and candesartan at different dosages in sequential concentrations (CI>1.1).The morphology imaging of neuron cells after treatment reveals enhanced neuronal cell morphology when using combination Taxol and candesartan. In conclusion, candesartan exhibits the potential to mitigate the cytotoxicity effect of Taxol chemotherapy.